Pendampingan Dan Pelatihan Pijat Laktasi Dan Teknik Relaksasi Hypnobreastfeeding Bagi Ibu Menyusui Di Puskesmas Kecamatan Koja Jakarta Utara - Sunarti, Nina; Supriyono, Ragil; Sofiah, Wiwik (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2024)
The postpartum period is the first six weeks after giving birth, which will be a very exciting moment, but also a period of adjustment and healing for the mother. During these weeks, the mother will bond with the baby and they will also undergo postnatal check-ups. Postpartum mothers will adapt both physiologically and psychologically to everyday life. After giving birth, it has its own challenges, especially if you are a new mother. One important thing that cannot be avoided is that mothers must go through phases of change in their physiology and psychology. The aim is to provide education and basic skills training to postpartum mothers to prepare them for the process of breastfeeding their babies at home. This activity was carried out on September 2024 at the Koja District Health Center. Participants in this activity were postpartum mothers on days 1-2 and pregnant women in the third trimester. The methods used in this activity are health training, discussion and practice of lactation massage and hypnobreastfeeding techniques. Assessment is carried out through pre-test and post-test activities carried out by trained staff to provide basic skills regarding lactation massage and hypnobreastfeeding techniques. This evaluation resulted that postpartum mothers and pregnant women have a high level of understanding and skills in lactation massage procedures and hypnobreastfeeding techniques. Mothers are expected to be able to apply the skills they have learned and become peer educators in their environment. Masa nifas adalah masa selama enam minggu pertama setelah melahirkan, Dimana akan menjadi moment yang sangat menggembirakan, tetapi juga merupakan periode penyesuaian dan penyembuhan bagi ibu. Selama minggu-minggu ini, ibu akan terikat dengan bayi dan mereka juga akan menjalani pemeriksaan pasca melahirkan. Ibu nifas akan menyesuaikan diri baik dari segi fisiologi maupun psikologis dengan kehidupan sehari-hari. Setelah melahirkan, hal tersebut memiliki tantangan tersendiri, terutama jika kamu seorang ibu baru. Salah satu hal penting yang tidak bisa di hindari adalah ibu harus melawati fase perubahan fisiologi dan psikologinya. Tujuannya adalah untuk memberikan pendidikan dan pelatihan keterampilan dasar pada ibu nifas untuk mempersiapkan proses menyusui bayinya saat dirumah. Kegiatan ini dilakukan pada tanggal 15 September 2023 bertempat di Puskesmas Kecamatan Koja. Peserta pada kegiatan ini ibu nifas hari ke 1-2 dan ibu hamil Trimester III sebanyak 15 orang. Metode yang digunakan dalam kegiatan ini adalah pelatihan Kesehatan, diskusi dan praktik pijat laktasi dan tehnik hipnobreastfeeding. Penilaian dilakukan melalui pre-test dan post-test kegiatan yang dilakukan oleh para pengabdi yang terlatih untuk memberikan keterampilan dasar tentang pijat laktasi dan tehnik hipnobreastfeeding. Evaluasi tersebut menghasilkan bahwa ibu nifas dan ibi hamil memiliki tingkat pemahaman dan keterampilan yang tinggi dalam prosedur pijat laktasi dan tehnik hipnobreastfeeding, Para ibu diharapkan dapat menerapkan keterampilan yang telah dipelajarinya dan menjadi peer pendidik di lingkungannya.